A biomimetic SiO2@chitosan composite as highly-efficient adsorbent for removing heavy metal ions in drinking water. (January 2019) - Liu, Jinyun; Chen, Yu; Han, Tianli; Cheng, Mengying; Zhang, Wen; Long, Jiawei; Fu, Xiangqian
Abstract: Highly efficient adsorbents for drinking water purification are demanded since the contaminants are generally in a low concentration which makes it difficult for conventional adsorbents. Herein, we present a novel biomimetic SiO2 @chitosan composite as adsorbent with a high adsorption capability towards heavy metal ions including As(V) and Hg(II). The hollow leaf-like SiO2 scaffold within the adsorbent has a stable chemical property; while on the surface SiO2, the chitosan nanoparticle provide a large amount of active sites such as amino and hydroxyl groups for adsorbing heavy metal ions. The special SiO2 structure also prevents the agglomeration and loss of chitosan, which enables the efficient contact between the functional groups of chitosan and heavy metal ions. The SiO2 @chitosan composite exhibits maximum adsorption capacities of 204.1 and 198.6 mg g −1 towards Hg(II) and As(V), respectively. In addition, the removal efficiency reaches over 60% within 2 min. The adsorption performance enables the presented biomimetic adsorbent suitable for adsorbing low-concentration heavy metal ions, especially possessing a promising potential for drinking water purification. Graphical abstract: Image Highlights: A unique biomimetic SiO2 @chitosan composite adsorbent is prepared. Leaf-like SiO2 @chitosan shows high adsorption performance toward As(V) and Hg(II). Agglomeration and loss of adsorbents are reduced by biomimetic structure.